2018
DOI: 10.1080/08912963.2018.1444761
|View full text |Cite
|
Sign up to set email alerts
|

The Quaternary plant fossil record from the volcanic Azores Archipelago (Portugal, North Atlantic Ocean): a review

Abstract: Plant fossils are known from the Azores Islands, yet poorly studied. We present a comprehensive bibliographical review for the archipelago. A first pre-scientific reference dates from late fifteenth century, while the first scientific description was reported in 1821, accounting for trunks in pyroclastic units and silicified plants within hydrothermal deposits. Throughout the second-half of the nineteenth century and the first-half of the twentieth century, prospection by naturalists and geological mapping wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…In these cases, island colonization is expected to have been rapidly followed by diversification within the island setting (Kim et al, 2008). Such a pattern of diversification is often triggered by inter-island dispersal, but it may also occur within single islands over short time intervals (Garot et al, 2019;Saro et al, 2019). When all extant populations/taxa are island Yan et al, 2018), the stem age estimate (8.0 Myr, 95% HPD = 6.8-10.3) suggests an old split between a mainland East Asian clade and the island lineage.…”
Section: Stem and Crown Ages Of Island Lineages As Proxies For Colonization Timementioning
confidence: 99%
“…In these cases, island colonization is expected to have been rapidly followed by diversification within the island setting (Kim et al, 2008). Such a pattern of diversification is often triggered by inter-island dispersal, but it may also occur within single islands over short time intervals (Garot et al, 2019;Saro et al, 2019). When all extant populations/taxa are island Yan et al, 2018), the stem age estimate (8.0 Myr, 95% HPD = 6.8-10.3) suggests an old split between a mainland East Asian clade and the island lineage.…”
Section: Stem and Crown Ages Of Island Lineages As Proxies For Colonization Timementioning
confidence: 99%
“…Immigration to Madeira Island from the Azores seems less probable since geochronological data shows that 1.3 Ma ago, most Azorean islands had not emerged yet. The only subaerial edifices available as source were Santa Maria Island and, less probably, the coeval São Jorge (1.3 Ma) or Corvo (1.5-1.0 Ma) islands (see Góis-Marques & al., 2019b and references therein). Désamoré & al.…”
Section: ■ Resultsmentioning
confidence: 99%
“…To date, no macrofossils attributable to the WPBH are known from the Macaronesian islands. This is mostly due to the infrequent palaeobotanical research performed in these islands (Góis‐Marques & al., 2019b; Góis‐Marques, 2020), due to the supposed idea that volcanic islands lack a well‐preserved and palaeobiological informative terrestrial fossil record (Anderson & al., 2009). However, other Erica fossils such as E. arborea L. were described from Madeira Island (Góis‐Marques & al., 2018) and a doubtful mention of E. arborea does exist for São Miguel Island (Góis‐Marques & al., 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…This would place H-III in the Azores before that date, although a more recent origin of these private haplotypes cannot be ruled out. Góis-Marques et al [ 111 ] concluded a Pleistocene–Holocene age for all plant fossils described in the Azores. Vandenboschia speciosa could have arrived to the Azores at Santa Maria Island (~6 Ma), the only island older than 1.5 Ma (reviewed by [ 108 ]).…”
Section: Discussionmentioning
confidence: 99%